Response of turmeric (Curcuma domestica Val.) to in vivo and in vitro pollination - Nybe, D Renjith, P A Valsala, E V (Journal of Spices and Aromatic Crops, 2001)
Seed set and development were obtained through in vivo pollination in three combinations of short duration turmeric cultivars and these were not observed in crosses of medium duration cultivars and short x medium duration cultivars. The fruit developed after in vivo pollination was a thick walled trilocular capsule. It took 20-22 days for development and ripening. Arilled seeds are triangular with two seed coats. The seeds are filled with massive endosperm and the embryo is seen oriented towards the chalazal end of the seed. In the in vitro pollination studies, culture establishment and ovule development were obtained in half strength MS + NAA 0.5 mg l-1 with BAP and kinetin at 1 mg l-1 each. Among the various methods of pollination tried, ovule seed-l development was observed in the intra ovarian, placental and modified placental pollination techniques. In the in vitro developed seed, the endosperm development was not complete. The aforesaid in vitro techniques need refinement with respect to medium and other requirements for the germination of in vitro produced seeds.